Apakah Fenomena Kurva Phillips Terjadi di Kalimantan Selatan? Pemodelan Autoregressive Distributed Lag (ARDL) pada Inflasi dan Pengangguran - Ahmadi Murjani (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2022)
The government's policies aimed at controlling inflation and reducing unemployment are two essential things. On the other hand, the short-run interaction of inflation and unemployment depicted in the Phillips Curve makes the policies more dilemmatic due to the trade-off between inflation and unemployment. Thus, the examination of inflation control and unemployment is needed. This research aims to investigate the relationship between inflation and unemployment. Based on the previous research that found mixed results, this research is distinctive from others by utilizing the ARDL bounds testing model applied to the South Kalimantan data from 1986 to 2021. Some crucial findings are achieved. First, the Phillips Curve can be found in South Kalimantan in the short run. Second, inflation affects unemployment but not vice versa. Third, inflation and unemployment are cointegrated in the long run. Hence, inflation control and reducing unemployment will face a trade-off impact in the short run.